Indicadores de restauração ecológica em áreas atingidas por rejeito de minério de ferro na bacia do Rio Doce - Andrade, Mariana Miranda (2021)
There are several impacts caused by mining operations. As a result of this activity, the rupture of the Fundão dam is considered the biggest environmental disaster in Brazil and one of the biggest environmental disasters on the planet. Since its rupture, several measures have been adopted to repair the damage to ecosystems, with great concern about the affected areas and the process of their restoration. Thus, practices aimed at evaluating and monitoring restoration become essential, whose aim is to verify the progress of this process, reinforcing the need for studies like this one, which aim to evaluate the restoration of areas affected by the dam failure. This work is divided into chapters, containing a general review of the topic addressed (Chapter 1), and the selection of ecological indicators and adjustment of an equation to evaluate the restoration of areas affected by tailings in the Rio Doce basin (Chapter 2). Areas undergoing restoration along the Rio Doce basin, in the municipalities of Barra Longa and Mariana, Minas Gerais, which were affected by the tailings wave in the Fundão dam failure in 2015, were evaluated. transects with 10 meters of width and variable length depending on the area under restoration. In each transect, four plots of 2 x 10 meters were allocated to evaluate natural regeneration and collect other indicators. The number of transects was stipulated according to the size of the area and the extension of the area along the watercourse. To compare reference areas and areas in the process of restoration, select indicators that best explain the trajectory of restoration and model an equation to quantify restoration, data from the following ecological indicators were used: density of individuals in the arboreal stratum and in natural regeneration , diversity of both strata using the Shannon index, mean height and basal area of the tree stratum, canopy cover, amount of biomass, soil cover attributes and soil chemical attributes. By the descriptive analysis and average comparison of all the evaluated ecological indicators, the reference areas showed superiority when compared to the restoration areas. Using a mixed generalized linear model adjusted for maximum likelihood, it was possible to select five ecological indicators (diversity by the Shannon index of the arboreal stratum, average height of the arboreal stratum, percentage of canopy cover and of soil cover by litter, and soil pH ), which presented significance (p-value) of less than 0.001, and generated an equation with a pseudo-R² of approximately 98%. The generated equation proved to be efficient and adequate to evaluate the progress of the restoration process of areas affected by iron ore tailings, with great application capacity because it is parsimonious. Keywords: